Evaluation of the Effectiveness of Ethnoscience-Based Project-Based Learning Model in Improving Understanding of Biotechnology Concepts through a Systematic Literature Review - Hamdiyah Hamdiyah; Dyah Rini Indriyanti; Novi Ratna Dewi (MASI Mandiri Edukasi, 2026)
This study aims to evaluate the effectiveness of the Ethnoscience-based PjBL model in improving the understanding of Biotechnology concepts through a systematic literature review. The research method uses a Systematic Literature Review (SLR) that follows the PRISMA standard, with data sources obtained from the Scopus and Google Scholar databases for the period 2013–2025. A total of 15 articles that met the inclusion criteria were analyzed using a bibliometric approach and qualitative thematic synthesis. The results of the study show that PjBL-Ethnosains consistently provides a significant improvement in the mastery of Biotechnology concepts across cognitive, affective, and psychomotor domains. Adaptive models such as CEL-BaDiS and CEL-BaDiS Up resulted in increased high-level thinking skills, including creativity and problem-solving, with gains reaching the medium-high category. In conclusion, Ethnoscience-based PjBL effectively strengthens understanding of Biotechnology concepts by integrating local cultural context into the scientific inquiry process. This study suggests developing a PjBL-Ethnoscience model with a more explicit syntax and rigorous experimental testing to produce a more comprehensive quantitative effect measure.